Development of a Lobster-Inspired Underwater Microrobot. (16th January 2013) - Shi, Liwei; Guo, Shuxiang; Mao, Shilian; Li, Maoxun; Asaka, Kinji
Biomimetic underwater microrobots are of great interest for underwater monitoring operations, such as pollution detection and video mapping in restricted underwater environments. Generally speaking, compact structure, multi-functionality, flexibility and precise positioning are considered incompatible characteristics for underwater microrobots. Nevertheless, we have designed several novel types of bio-inspired locomotion, using ionic polymer metal composite (IPMC) and shape memory alloy (SMA) actuators. We reviewed a number of previously developed underwater microrobot prototypes that were constructed to demonstrate the feasibility of these types of biomimetic locomotion. Based on these prototypes, we summarized the implemented techniques and available results for efficient and precise underwater locomotion. In order to combine compact structure, multi-functionality, flexibility and precise positioning, we constructed a prototype of a new lobster-like microrobot and carried out a series of experiments to evaluate its walking, rotating, floating and grasping motions. Diving/surfacing experiments were performed by electrolyzing the water around the surfaces of the actuators. Three proximity sensors were installed on the microrobot to detect an object or avoid an obstacle while walking.